Pengaruh Model Kooperatif Teams Games Tournament (TGT) Terhadap Hasil Belajar PAI - Hasyim, Aika; Hermawan, Iwan; Aini Farida, Nur (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine whether there is an effect of the Teams Games Tournament (TGT) Model on student learning outcomes in class X TKR 1 at SMK Negeri 1 Cilamaya. The approach in this study uses a quantitative approach with experiments. The results of the data analysis test on the use of the TGT Model (X) on learning outcomes (Y). The results of the descriptive analysis show that the data values ​​are normally distributed with the average pretest score for the experimental class being 68.21 and the average posttest score being 81.07. Meanwhile, the control class obtained an average pretest score of 63.04 and a posttest score of 71.25. The results of the t-test through SPSS 25 obtained a significance value of 0.00 <0.05, meaning that there is an average difference between the pretest and posttest of student learning outcomes. It can be concluded that Ha is accepted and Ho is rejected. This shows that the Team Games Tournament (TGT) cooperative learning model has an influence on the learning outcomes of class X TKR 1 SMKN 1 Cilamaya.